Selection of suitable reference lncRNAs for gene expression analysis in Osmanthus fragrans under abiotic stresses, hormone treatments, and metal ion treatments - Zhang, Yingting; Yan, Qingyu; Xia, Hui; Zeng, Xiangling; Yang, Jie; Cai, Xuan; Li, Zeqing; Chen, Hongguo; Zou, Jingjing (Frontiers in Plant Science, 2025)
IntoductionOsmanthus fragrans, a well-regarded traditional flower in China, holds extensive applications in gardening, food, cosmetics, and traditional Chinese medicine. Despite its importance, research on long non-coding RNAs (lncRNAs) in O. fragrans has been constrained by the absence of reliable reference genes (RGs).MethodsWe employed five distinct algorithms, i.e., delta-Ct, NormFinder, geNorm, BestKeeper, and RefFinder, to evaluate the expression stability of 17 candidate RGs across various experimental conditions.Results and discussionThe results indicated the most stable RG combinations under different conditions as follows: cold stress: lnc00249739 and lnc00042194; drought stress: lnc00042194 and lnc00174850; salt stress: lnc00239991 and lnc00042194; abiotic stress: lnc00239991, lnc00042194, lnc00067193, and lnc00265419; ABA treatment: lnc00239991 and 18S; MeJA treatment: lnc00265419 and lnc00249739; ethephon treatment: lnc00229717 and lnc00044331; hormone treatments: lnc00265419 and lnc00239991; Al3+ treatment: lnc00087780 and lnc00265419; Cu2+ treatment: lnc00067193 and 18S; Fe2+ treatment: lnc00229717 and ACT7; metal ion treatment: lnc00239991 and lnc00067193; flowering stage: lnc00229717 and RAN1; different tissues: lnc00239991, lnc00042194, lnc00067193, TUA5, UBQ4, and RAN1; and across all samples: lnc00239991, lnc00042194, lnc00265419 and UBQ4. The reliability of these selected RGs was further validated by analyzing the expression patterns of lnc00003036, lnc00126603, and lnc00250780. This study represents the first comprehensive evaluation of lncRNA RG stability in O. fragrans, significantly enhancing the accuracy and depth of lncRNA expression analyses in this species, contributing to advancements in plant stress resistance breeding and improving environmental adaptability.